Parasitos intestinais em crianças de centros municipais de educação infantil de áreas socioeconomicamente desenvolvidas em fronteira brasileira - Ferreira, Arthur Luiz de Campos (2018)
Foz do Iguassu, located on the triple frontier, has characteristics that results from series of transformations which occurred mainly in the 70's and 90's. These transformations affected distinct aspects of the local reality, such as job creation and unbridled population growth. Due to this, many women were inserted in the labour market, leaving their children in the Municipal Centers for Children's Education (CMEIs). Many children spend a large time of their time in these institutions, which plays an important role in developing children’s intellectual, physical, social and psychological. Unfortunately, however, these children attending CMEIs are more susceptible to infections, due to direct interpersonal contact provided by these collective environments. The intestinal parasitoses are considered a serious public health problem in Brazil, occurring predominantly in areas with hygienic-sanitary precarious conditions and human clusters. Intestinal parasites have close relationship with socio-demographic and environmental factors. Capable of causing diarrhea, anemia and malnutrition, compromising physical and intellectual development, especially in children. Thus, this study objective is to verify the frequency of intestinal parasitosis in children of two Municipal Centers for Children's Education from Foz do Iguassu, State of Parana, in areas socioeconomically developed, and evaluate socioeconomic aspects, sanitary aspects and hygienist aspects of the children studied and their guardians. The present study is a field research which addresses a quantitative approach. The population of this study was consisted of all pre-school children, aged 3 to 5 years, enrolled in CMEIs A and B, and their parents and/or guardians where it was worked with convenience sampling. A parasitological examination of feces was collected and later processed in the Environmental Laboratory located in Itaipu Hydroelectric Power Plant, using Hoffmann Spontaneous Sedimentation Method and techniques of centrifugation-flotation by saturated solution of zinc sulfate (Faust). Furthermore, a questionnaire with 19 closed questions regarding socioeconomic and hygienic-sanitary conditions was applied to children’s parents and/or guardians. The data were analyzed by the BioEstat 5.3® program and, considering the level of significance in 5%. A total of 96 fecal samples were analyzed between September and November 2016. The prevalence of intestinal parasites was 17.7%, the most frequent being Endolimax nana (12.5%) and Giardia duodenalis (6.2%), in addition to a case of biparasitism (1.1%), and without a presence of helminths. The most affected groups of children were male (64.7%) and aged 5 years (41.2%). The socioeconomic profile showed that the schooling level of the parents who the children were parasitized was that 35.3% had completed high school (p> 0.05), and 35.3% had incomplete high school education (p> 0.05); 35.3% with family income of 2 to 3 minimum salary (p> 0.05); 100.0% (p <0.05) of the families received tap water, 58.8% (p <0.05) treated with chlorine, and 76.4% (p <0.05) their human waste through the sewage system; about children's hygiene habits, 94.1% (p <0.05) washed their hands before eating and after using the toilet, and 11.7% washed their hands only with water; regarding health care of these children, 70.6% (p> 0.05) had already had parasitological feces examination, only 11.7% (p <0.05) of the parasitized children had abdominal pain, nausea or frequent vomit, 5.8% (p <0.05) had weight loss, 70.6% (p <0.05) had formed feces and in 88.2% (p <0.05) of the cases already had used anti-parasitic. These variants may have influenced the low frequency of parasitism. However, the highlighted number for the low frequency of parasitoses related to the characteristics of personal hygiene and food habits, where that 70.6% (p <0.05) washed their hands after changing diapers and washed with only water the raw consumed food, and 17.6% (p <0.05) reported having a home garden. The study showed a low prevalence of intestinal parasites in children due to the favorable conditions of sanitation found in the houses. Even though the presence of a non-pathogenic parasite such as Endolimax nana is prevalent, its notification is important, because it has the same transmission mechanism of pathogenic parasites. Considering that the use of anti-parasites without medical prescription, the population orientation, mainly in relation to the risk of self-medication and sanitary education, is necessary.